Effective long-term hemofiltration in contrast-induced nephropathy - E. A. Tabakyan; R. S. Akchurin; A. Yu. Zaruba; E. E. Vlasova (Кардиоваскулярная терапия и профилактика)
Aim. To analyse the causes of contrast-induced nephropathy (CIN) after coronary angioplasty (CAP), as well as the potential of long-term hemofiltration in CIN treatment. Material and methods. CIN risk was assessed by total score, as recommended by Barrett ВJ and Parfrey PS (2006). CAP with stent implantation was performed via femoral access, with hypoosmolar contrast ultravist 370. Hemofiltration was performed with the Diapact®CRRT device (substitution volume >30 ml/kg/h; Duosol® solution in bicarbonate buffer; heparin anticoagulation (10 U/kg/h) under activated clotting time control). Venous levels of hematocrit, K, Na, glucose, pH, bicarbonate, and lactate were controlled every 2-3 hours. Results. In a 71-year-old male patient with coronary heart disease (CHD) and post-infarction cardiosclerosis, the indications for CAP included myocardial ischemia and recurrent myocardial infarction (MI) risk. Concomitant diabetes mellitus was treated with novonorm and metformin. At baseline, serum creatinine level was 109 mkmol/l and glomerular filtration rate (GFR) — 50,5 ml/min/1,73 m2 , with moderate CIN risk. Balloon dilatation of circumference artery and blunt edge artery (BEA), obtuse marginal artery (OMA) stenting, OMA dilatation and stenting were performed. In total, 400 ml of contrast were used. Twenty-four hours later, creatinine level increase by 25 % was observed, with no effect from saline hydration. After 48 h, further increase in creatinine concentration, GFR <15 ml/min/1,73 m2 , and oligouria were observed. Long-term hemofiltration resulted in CIN regression. Conclusion. Long-term hemofiltration could have a crucial role in CIN treatment, in case of severe acidosis, oligouria, and GFR reduction <15 ml/min/1,73 m2 . Before the contrast administration, all necessary measures should be taken, to prevent CIN development.